Investor-driven corporate finance: Evidence from insurance markets - Christian Kubitza (European Central Bank (ECB), 2023)
I study the causal effect of bond investor demand on the financing and investment decisions of nonfinancial firms using granular data on the bond transactions of U.S. insurance companies. Liquidity inflows from insurance premiums combined with insurers' persistent investment preferences identify bond demand shifts, which raise bond prices and reduce firms' financing costs. In response, firms issue more bonds, especially when they have well-connected bond underwriters. The proceeds are used for investment rather than shareholder payouts, particularly by financially constrained firms. The results emphasize that bond investors significantly affect corporate financing and investment decisions through their price impact.
Keywords: G12; G22; G23; G3; G32; 330; nstitutional Investors; Insurance; Corporate Bonds; Corporate Investment